2009
DOI: 10.2203/dose-response.09-027.hamblin
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Dose Response in Low Level Light Therapy

Abstract: ᮀ The use of low levels of visible or near infrared light for reducing pain, inflammation and edema, promoting healing of wounds, deeper tissues and nerves, and preventing cell death and tissue damage has been known for over forty years since the invention of lasers. Despite many reports of positive findings from experiments conducted in vitro, in animal models and in randomized controlled clinical trials, LLLT remains controversial in mainstream medicine. The biochemical mechanisms underlying the positive eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
621
1
35

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 907 publications
(692 citation statements)
references
References 113 publications
35
621
1
35
Order By: Relevance
“…Therefore, since the dose-response effect varies according to the set of irradiation parameters (21), it may be suggested that a higher frequency of exposure of MDPC-23 cells to LED exceeded the threshold of biological tolerance of these cells, leading to a reduction in their metabolism. Previous studies that evaluated the bio-stimulatory effects of light sources have observed such biphasic effect (1,15,20). These studies have shown that the effect of light is not linear, being dependent on the frequency of application and energy doses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, since the dose-response effect varies according to the set of irradiation parameters (21), it may be suggested that a higher frequency of exposure of MDPC-23 cells to LED exceeded the threshold of biological tolerance of these cells, leading to a reduction in their metabolism. Previous studies that evaluated the bio-stimulatory effects of light sources have observed such biphasic effect (1,15,20). These studies have shown that the effect of light is not linear, being dependent on the frequency of application and energy doses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the power density has a direct influence on the effect of light by the generation of a two-stage dose-response effect, in which inhibition of stimulatory effects is achieved when the threshold of energy received by the cell is exceeded (15,20). Therefore, since the dose-response effect varies according to the set of irradiation parameters (21), it may be suggested that a higher frequency of exposure of MDPC-23 cells to LED exceeded the threshold of biological tolerance of these cells, leading to a reduction in their metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic effects of LLLT have been reported, being associated with production of anti-apoptotic, pro-proliferative, antioxidant, and angiogenic factors [31][32][33] . LLLT also known as photobiomodulation, is an emerging therapeutic approach in which cells or tissues are exposed to low-levels of red and near-IR light.…”
Section: Discussionmentioning
confidence: 99%
“…Light at this wavelength is known to be absorbed by cytochrome C oxidase and other molecules, stimulating ATP synthesis and affecting ROS production, among numerous other activities at the cellular, tissue and whole organism level (16). The caveat however is that the light dose and dose rate are important and that all cell and tissues are not equally responsive to photoradiation (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%